Polymer Brushes by Grafting to Reaction in Melt: New Insights into the Mechanism. Issue 5 (22nd December 2022) - Chiarcos, Riccardo; Perego, Michele; Laus, Michele
Abstract: Ultrathin films of end‐tethered polymers, generally indicated as polymer brushes, have gained great interest for their ability to modify the surface interaction with the surrounding environment. One of the most common strategies to obtain polymer brushes is based on the reaction of end‐functional polymers with the substrate surface, in a process defined as grafting to. The two advantages of grafting to reactions are i) the functional polymer is prepared before the grafting reaction and therefore can be fully characterized and ii) the reaction has a self‐limiting nature, meaning that the number of grafted chains converges to a plateau value after a sufficiently long reaction time. The limit value of grafted chains is governed by the molecular weight of the employed polymer, thus allowing a fine control of the brush thickness. In this work, the origin of the self‐limiting nature of the grafting to reaction is discussed comparing theoretical models with experimental data. Furthermore, the kinetics of the process is discussed, considering both polymer diffusion and end‐group reactivity as the main drivers of the grafting to process. Finally, the effect of molecular weight dispersity on the brush characteristics is highlighted. Abstract : The reaction of end‐functional polymers on substrates is generally defined as grafting to reaction and plays a primary role in the synthesis of polymer brushes, particularly due to its self‐limiting nature. In this work, the fundamental aspects of grafting to processes are discussed.